Rape in the Republic, 1609-1725 : Formulating Dutch Identity. - Pipkin, Amanda C. (Studies in medieval and Reformation traditions., 2013)
By examining depictions of rape in pamphlets, plays, poems, and advice manuals, this book underscores the significance of sex and gender in the construction of Dutch identity during the period of the Revolt of the Netherlands and beyond.